(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2012)
The article deals with the notion of intertextuality in information texts. The author analysis expressive language means, including allusions and applications that demonstrate the intertextual properties, taking into account the structural and semantic aspects.